Degas et le cheval - Mariel Oberthur (In Situ)
Degas and the horse. To study the way horses moved, long before Muybridge’s celebrated photographs were published in 1878, the painter Degas visited his friend Paul Valpinçon in Normandy, at Ménil-Hubert near the Haras du Pin stud farm. It was there, in 1861, that he drew in his notebooks, constituting a corpus from which he drew inspiration for modelling wax horses used for his pictures done in oil or pastel. This research into movement is an essential element in Degas’ work.